$\boldsymbol {L^{p}}$ REGULARITY OF THE SZEGÖ PROJECTION ON THE SYMMETRISED POLYDISC. Issue 3 (12th December 2022) - HAN, KAIKAI; TANG, YANYAN
Abstract: We consider the $L^{p}$ -regularity of the Szegö projection on the symmetrised polydisc $\mathbb {G}_{n}$ . In the setting of the Hardy space corresponding to the distinguished boundary of the symmetrised polydisc, it is shown that this operator is $L^{p}$ -bounded for $p\in (2-{1}/{n}, 2+{1}/{(n-1)})$ .